Health-Related Quality of Life in Overweight/Obese Children Compared With Children With Inflammatory Bowel Disease. (July 2015) - Faus, Amy L.; Turchi, Renee M.; Polansky, Marcia; Berez, Andrea; Leibowitz, Karen L.
Purpose . This study examined the health-related quality of life (HRQOL) of pediatric patients with overweight/obesity compared with that of patients with inflammatory bowel disease. Methods . Differences between disease groups in their PedsQL 4.0 HRQOL survey scores were analyzed using unpaired t tests and analyses of variance. Results . Scores of patients with overweight/obesity were as low as scores of patients with inflammatory bowel disease. Parent/guardian-proxy social functioning scores of the overweight/obese group were statistically significantly lower than scores of the inflammatory bowel disease group, and the parents/guardians reported significantly lower HRQOL scores than the patients. Conclusions . Overweight/obese children have HRQOL scores as impaired as those of children with inflammatory bowel disease. According to proxy-reported scores, overweight/obesity is associated with lower social functioning. Thus, it is important for health care providers to recognize obesity's relationship to patients' psychosocial health and provide holistic care that addresses the severity of this disease.